Fatigue and Fracture Mechanics of Marine Structures - Ehlers, Sören; Braun, Moritz (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Fatigue and fracture are important design criteria for marine structures subjected to static and cyclic loading. In particular, the ability to ensure structural integrity under all design conditions is of the utmost importance for the safety of humans and the environment. Many efforts have been made to develop fatigue and fracture mechanics methods in recent decades; however, discrepancies between predicted and actual strength remain due to various reasons. Hence, this Special Issue aims to collect descriptions of fatigue and fracture mechanical behaviour of marine structures. Studies demonstrating novel methods (either analytical, empirical or numerical), as well as presentations of case studies or innovative test studies, were invited. This includes considerations of parameters which have a large influence on fatigue and fracture behaviour of materials, welded joints or structural components, such as loading conditions, scale effects, etc.